Review on Anastomotic Leak Rate after ICG Angiography during Minimally Invasive Colorectal Surgery - Tsanko Yotsov; Martin Karamanliev; Svilen Maslyankov; Dobromir Dimitrov (Journal of Biomedical & Clinical Research)
Colorectal cancer is the 3rd most common type of cancer worldwide. The most devastating complication after colorectal surgery remains the anastomotic leak (AL). Many techniques have been developed to reduce its rate. One such new method is perfusion angiography using indocyanine green (ICG). A literary search in PUBMED on 1.03.2021 for full-text English articles published between 2014 and 2021 was performed. ICG, colorectal cancer, and angiography were the keywords we used. The review was performed following the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The literature search yielded 27 results when searching the database of PUBMED with the above keywords. Twenty-one out of 27 identified articles were included. Six were excluded from the analysis – four case reports, one review on the evolution of treating gastrointestinal cancers, and one containing no information on AL rate with ICG. One included article was RCT, sixteen were cohort studies, and four were meta-analyses or reviews. All articles reported a reduction in the anastomotic leak rate. However, the reduction was significant only in nine of them. Anastomotic leak is a severe complication and a subject of extensive research. Perfusion angiography with ICG is a step towards predicting and preventing AL, although it does not guarantee success in all cases.